AI: profili giuridici. Intelligenza Artificiale: criticità emergenti e sfide per il giurista (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The research aims at exploring the main legal issues triggered by the implementation of Artificial Intelligence systems, with a view to identifying possible solutions for regulators and lawmakers at national and supranational level. The study moves from a comprehensive overview covering the existing soft law instruments, the core areas captured in academic speculation and the latest developments in case law. It then separately addresses selected sensitive issues that should be on public and private policymakers’ agenda, most notably: the governance of AI; the impact of AI systems on public law; the relationship between AI systems and private and criminal law as well as procedural law. For each of these areas, the research analyzes how the rise of AI systems calls into question well established legal categories and which remedies lawmakers and regulators should take into account to reconcile the need to foster technological developments and that of protecting fundamental rights.
Keywords: Artificial Intelligence; fundamental rights; disruptive technologies; regulation; governance